Implementation of Collage Techniques in the SBDP Subject Using Natural Materials to Enhance the Creativity of 4th Grade Students - Ruskamini; Hety Diana Septika; Muhlis; Rosita Putri Rahmi Haerani (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the fact that the creativity of students at SDN 010 Samarinda Seberang in the subject of Arts, Culture, and Crafts is still relatively low. The research problem is how the collage technique can improve the creativity of fourth-grade students at SDN 010 Samarinda Seberang in the 2025/2026 academic year. Therefore, the purpose of this study is to determine the effectiveness of the collage technique in enhancing the creativity of fourth-grade students at SDN 010 Samarinda Seberang in the 2025/2026 academic year. This type of research is Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of two meetings. The research procedure includes four stages: planning, implementation, observation, and reflection. The subjects of this study were 31 fourth-grade students of class IV B at SDN 010 Samarinda Seberang. The data collection techniques used were observation, interviews, questionnaires, assessment sheets, and documentation. The data analysis techniques applied were averages, percentages, and graphs. The results of the study showed an improvement in the students’ average scores from the pre-cycle score of 74.83 with a mastery percentage of 29.03%, or 9 students achieving mastery. In cycle I, there was an increase of 3.67 points from the pre-cycle, with an average score of 77.58 and a mastery percentage of 48.38%, or 15 students achieving mastery. In cycle II, there was a significant increase of 10.18 points from cycle I, with an average score of 85.48 and a mastery percentage of 83.87%, with 26 students achieving mastery and 5 students not yet achieving mastery. This result met the expected success indicator of 80%. Based on these findings, it can be concluded that the implementation of the collage technique improved students’ creativity in the subject of Arts, Culture, and Crafts at SDN 010 Samarinda Seberang.